Can absent leadership be positive in team conflicts?: An examination of leaders' avoidance behavior in China. Issue 2 (10th April 2017) - Yang, Inju; Li, Ming
Abstract : Purpose: This paper aims to examine how leaders' avoidance influences followers' attitudes and well-being in China. Although conflict avoidance is one of the most commonly used conflict resolution styles in China, there has surprisingly been no explicit investigation of the effects of leaders' avoidance. Design/methodology/approach: Data were collected from 245 subordinates in three large companies in the People's Republic of China through an online survey. Multiple regression analysis was adopted to test three sets of competing hypotheses. Findings: Leaders' avoidance behavior is positively related to followers' perception of justice, supervisory trust and emotional well-being in Chinese organizations. Originality/value: This paper joins growing attempts to consider conflict management in the context of leadership. To the best of the authors' knowledge, this is the first study to examine empirically the relationships between a team leader's avoidance behavior and his or her subordinates' perceptions of justice, supervisory trust and emotional well-being in a single study. The findings are provoking by illustrating positive effect of leader's conflict avoidance behavior in China. This paper supports that conflict avoidance could be a sustainable rather than one-off strategy by a leader, and that identifying conditions (e.g. culture) that affect the outcomes of conflict avoidance is important.